Оценка естественной защищенности подзменых вод от загрязнения (на примере бассейна реки Прут в пределах Черновицкой области) - Ємчук, Тетяна; Арпуль, Оксана (My University, 2016)
The article deals with the relevance and prospects of estimation of natural protection which was carried out for the DRASTIC procedure. The basis of this method takes into account the seven major factors such as the groundwater depth, effective infiltration of water, aquifer lithology, soil texture, slope of the ground surface, rock lithology of the vadose zone, filtration coefficient of the aquifer. The research results allowed forming a database to assess the role and value of the criteria in the evaluation of the natural groundwater protection.
Keywords: естественная защищѐнность подземных вод; качество вод; подземные воды; загрязняющие вещества; охрана подземных вод